2022
DOI: 10.3390/cancers14051198
|View full text |Cite
|
Sign up to set email alerts
|

Actively Targeted Nanomedicines in Breast Cancer: From Pre-Clinal Investigation to Clinic

Abstract: Breast cancer is one of the most frequently diagnosed tumors and the second leading cause of cancer death in women worldwide. The use of nanosystems specifically targeted to tumor cells (active targeting) can be an excellent therapeutic tool to improve and optimize current chemotherapy for this type of neoplasm, since they make it possible to reduce the toxicity and, in some cases, increase the efficacy of antineoplastic drugs. Currently, there are 14 nanomedicines that have reached the clinic for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 210 publications
(227 reference statements)
0
24
0
Order By: Relevance
“…It is a 30 nm protein-based nanocompound formed by Transtuzumab, an anti-HER-2 humanized monoclonal antibody that is bound to DM-1 (emtansine, an antimicrotubular agent that blocks cellular division) [ 110 ]. Kadcyla TM , as a single therapy, is indicated for the adjuvant treatment of adult patients with HER2-positive early breast cancer who have residual invasive disease [ 111 ]. It is commonly used in combination with other antineoplastics for the treatment of HER-2-positive breast tumors.…”
Section: Approved Nanopharmaceuticals For Clinical Uses In Cancer The...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a 30 nm protein-based nanocompound formed by Transtuzumab, an anti-HER-2 humanized monoclonal antibody that is bound to DM-1 (emtansine, an antimicrotubular agent that blocks cellular division) [ 110 ]. Kadcyla TM , as a single therapy, is indicated for the adjuvant treatment of adult patients with HER2-positive early breast cancer who have residual invasive disease [ 111 ]. It is commonly used in combination with other antineoplastics for the treatment of HER-2-positive breast tumors.…”
Section: Approved Nanopharmaceuticals For Clinical Uses In Cancer The...mentioning
confidence: 99%
“…Furthermore, this binding also promotes HER-2 receptor degradation and activates the antibody-dependent cell-mediated cytotoxicity. It is used in combination with other antineoplastics for the treatment of HER-2-positive breast tumors [ 111 , 112 ].…”
Section: Approved Nanopharmaceuticals For Clinical Uses In Cancer The...mentioning
confidence: 99%
“…In this cohort of heavily treated m TNBC patients, sacituzumab govitecan was shown to be very well tolerated and to produce early and long-lasting therapeutic effects. PF-06647263, an ADC consisting of an anti-EFNA4 antibody linked to a calicheamicin payload, was shown to exhibit preliminary effects in some xenograft models (Fraguas-Sánchez et al, 2022). Ignacio et al implemented a first-inhuman study of PF-06647263 using every 3 weeks and every week regimens in patients with TNBC, ovarian cancer, and other advanced solid tumors (Garrido-Laguna et al, 2019).…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…In addition to the phagocytosis-based localisation of HSA-NC, much of the localisation of albumin nanoparticle-based chemotherapy is attributed to enhanced permeability and retention (EPR), by which the higher permeability of the blood vessels in tumours allows the extravasation of the nanoparticles into the tumour microenvironment, where retention is further enhanced by the lack of efficient lymphatic drainage [ 30 ]. However, the EPR theory has recently been described as too simplistic, and it has been demonstrated that there can be the transport of nanoparticles across intact endothelium [ 31 ].…”
Section: Design Challengesmentioning
confidence: 99%
“…HSA-NC is highly amenable to modification for specific targeting [ 23 , 30 ]. The vast range of possibilities include folate [ 32 ], peptides (e.g., Arg-Gly-Asp RGD peptides which bind α V β 3 integrin in neoangiogenesis) [ 33 ], and monoclonal antibodies (e.g., trastuzumab to target HER2-overexpressing breast tumour cells) [ 34 ].…”
Section: Design Challengesmentioning
confidence: 99%